Various aspects of soil microbial ecology as revealed by phospholipid fatty acid (PLFA) analysis. - Kotas, Petr (Jihočeská univerzita, 2018)
The PLFA profiling method was adopted and used to determine changes in microbial community structure and abundance along natural and human-induced environmental gradients. The presented studies were based on field sampling campaigns combined with targeted laboratory experiments. According to the aims of particular studies, microbial PLFA fingerprinting was combined with the auxiliary below- and aboveground ecosystem characteristics to identify the drivers of microbial responses to environmental changes or with 13C-labelling and metagenomics to obtain more complex information about running processes and involved microorganisms.
Various aspects of soil microbial ecology as revealed by phospholipid fatty acid (PLFA) analysis.
Keywords: phospholipid fatty acid; PLFA; soil microbial ecology; microbial community structure; phospholipid fatty acid; PLFA; soil microbial ecology; microbial community structure